Feedback control of stored energy and rotation with variable beam energy and perveance on DIII-D. (22nd May 2019) - Boyer, M.D.; Erickson, K.G.; Grierson, B.A.; Pace, D.C.; Scoville, J.T.; Rauch, J.; Crowley, B.J.; Ferron, J.R.; Haskey, S.R.; Humphreys, D.A.; Johnson, R.; Nazikian, R.; et al.
Abstract: Design and testing of a new method for real-time control on DIII-D using the new voltage and perveance variation capability of DIII-D's neutral beam injection system is presented. The approach enables control of power, torque, stored energy, and rotation without requiring pulse-width modulation of the beams. Such modulations are perturbative to experiments, can cause beam reliability problems, and could potentially damage or fatigue accelerator grids, especially looking forward to active control of long-pulse devices and reactors. The control algorithm accounts for beam line loss mechanisms and includes approaches that address the complexity of having three manipulated variables for each of the eight beams and compensate for the rate and magnitude limits affecting the voltage and perveance actuators. Results are presented that demonstrate the performance of the approach in the first feedback control experiments to use the expanded controllability of the DIII-D beams.